DEVELOPMENT OF AN INSTRUCTIONAL DESIGN MODEL USING BLENDED LEARNING AND COLLABORATIVE LEARNING TO IMPROVE MANDARIN PROFICIENCY IN PRC STUDENTS - Ma, Biyuan; Wanpen, Supratra; Kaewmanee, Theerapong (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The purposes of this research were: 1) to create an instructional design model using blended learning and collaborative learning strategies to improve the Mandarin Chinese proficiency of undergraduate students majoring in Primary Education, and 2) to assess the appropriateness of the developed instructional model. This research used a Research and Development (R&D) approach and was conducted in two phases. In Phase 1, data were collected through semi-structured interviews with five Mandarin Chinese experts and five Mandarin Chinese teachers, selected via purposive sampling. Additionally, a questionnaire was distributed to 248 undergraduate students majoring in Primary Education, who had previously studied Mandarin Chinese, to explore their learning problems and needs. Furthermore, 20 students were interviewed using open-ended questions and categorized into three groups based on academic performance: high, medium, and low. The data obtained from both experts and students were analyzed and used to design the preliminary instructional model. In Phase 2, experts who had earned their doctoral degrees and had three years of teaching experience evaluated the model’s content validity using a five-point rating scale to assess appropriateness. All of the instruments used were checked for their relevance according to the IOC. The results were as follows: 1) In the first phase, the biggest obstacles during the instructional process were the differences of language proficiency among students and the lack of instructional tools like speech laboratories. However, students showed a strong interest in education that includes technology. The model included ten components, and three instructional stages: pre-class, in-class, and after-class. 2) In the second phase, the analysis showed that all IOC values were higher than 1.0, and the overall appropriateness score was high, with an average of 4.05. This means that the instructional model development has a strong potential to effectively enhance the Mandarin Chinese proficiency of undergraduate students.